2021
DOI: 10.3233/jhd-200445
|View full text |Cite
|
Sign up to set email alerts
|

What is the Pathogenic CAG Expansion Length in Huntington’s Disease?

Abstract: Huntington’s disease (HD) (OMIM 143100) is caused by an expanded CAG repeat tract in the HTT gene. The inherited CAG length is known to expand further in somatic and germline cells in HD subjects. Age at onset of the disease is inversely correlated with the inherited CAG length, but is further modulated by a series of genetic modifiers which are most likely to act on the CAG repeat in HTT that permit it to further expand. Longer repeats are more prone to expansions, and this expansion is age dependent and tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 277 publications
(240 reference statements)
0
27
0
Order By: Relevance
“…Such diseases include HD (OMIM#143100), spinocerebellar ataxia type 1 (SCA1 OMIM#164400), SCA2 (OMIM#183090), SCA3 (OMIM#109150), SCA6 (OMIM#183086), SCA7 (OMIM#164500), SCA17 (OMIM#607136), and others. The age of onset of symptoms correlates with the length of the inherited CAG tract at the disease locus [132]. For the same inherited CAG size a broad range of onset age can occur, but less so within a given family [133], suggesting genetic modifiers of disease onset, independent of CAG tract size, must exist.…”
Section: Genetic Modifiers Of Cag/polyq Expansion Disease Onsetmentioning
confidence: 99%
“…Such diseases include HD (OMIM#143100), spinocerebellar ataxia type 1 (SCA1 OMIM#164400), SCA2 (OMIM#183090), SCA3 (OMIM#109150), SCA6 (OMIM#183086), SCA7 (OMIM#164500), SCA17 (OMIM#607136), and others. The age of onset of symptoms correlates with the length of the inherited CAG tract at the disease locus [132]. For the same inherited CAG size a broad range of onset age can occur, but less so within a given family [133], suggesting genetic modifiers of disease onset, independent of CAG tract size, must exist.…”
Section: Genetic Modifiers Of Cag/polyq Expansion Disease Onsetmentioning
confidence: 99%
“…The autosomal-dominant neurodegenerative disorder Huntington’s disease (HD) is caused by the expansion of a CAG repeat tract at the 5′ of the huntingtin gene above a critical threshold of ~35 repeats 1 . CAG tract expansion corresponds to an expanded polyglutamine tract of the Huntingtin (HTT) protein, which functions aberrantly compared to its unexpanded form 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Somatic instability in the cortex in HD brains is a predictor of age of onset 63 and increases with age 66 . Recently, it has been observed that individuals who lack a CAA interruption in the CAG repeat have a significantly earlier age of onset in HD as well as increased somatic instability 58 , 59 , 60 , 67 . Somatic instability is often linked to an altered DNA damage response.…”
Section: Somatic Instability and Dna Handling In Hdmentioning
confidence: 99%
“…* Line may have a slightly different name depending on the study or publication. ** The CAG repeat size listed here is an estimate of the number of contiguous CAG triplets and does not include CAA interruptions, which are likely to occur and have been identified in human 58 , 59 and mouse models 60 . *** To generate this list, we focused on the most prominent phenotypes reported between 2012 and 2022.…”
Section: Introductionmentioning
confidence: 99%